Silicone rubber / MOF vertical array hollow fiber composite membrane as well as preparation method and application thereof

By constructing a MOF functional layer and a metal oxide rod-shaped array on the surface of the polymer hollow fiber membrane, combining the crosslinking of silicon rubber, a silicon rubber/MOF vertical array hollow fiber composite membrane was prepared, which solved the problem of improving ethanol/water separation performance and achieved the goal of achieving Efficient ethanol/water separation breaks the separation layer inhomogeneity and gravity in traditional methods.

CN119186286AActive Publication Date: 2024-12-27BEIJING INST OF TECH

Patent Information

Application Number
CN202411363906.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-28
Publication Date
2024-12-27
Estimated Expiration
2044-09-28

AI Technical Summary

Technical Problem

In the prior art, the improvement of the ethanol/water separation performance of polymer hollow fiber membranes is limited, and how to further improve the separation performance of ethanol/water is of great significance.

Method used

By constructing a MOF functional layer on the surface of the polymer hollow fiber membrane and using metal oxide rods as templates, a MOF/metal oxide composite rod-like array was constructed, and combined with the cross-linking and curing of silicon rubber, a silicon rubber/MOF vertical array hollow fiber composite was prepared. membrane for efficient PV separation of ethanol/aqueous solutions.

Benefits of technology

The synchronous improvement of membrane permeability and selectivity is achieved, breaking the problem of separation layer inhomogeneity caused by gravity in traditional coating methods, enhancing the separation ability and selectivity of the membrane, and significantly improving the separation performance of ethanol/water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186286A_ABST
    Figure CN119186286A_ABST
Patent Text Reader

Abstract

The invention discloses a silicone rubber / MOF vertical array hollow fiber composite membrane and a preparation method and application thereof.The preparation method comprises the steps that a hollow fiber membrane is packaged to manufacture a shell-and-tube membrane module, and ZIF-8 seed crystals which are evenly distributed are prepared on the outer surface or the inner surface of a PVDF hollow fiber membrane; and injecting the ZnO precursor solution into a shell pass or a tube pass of the membrane module, and performing hydrothermal synthesis to obtain the PVDF hollow fiber membrane module on which the ZnO microrod array grows. Then injecting the ligand solution into a shell pass or a tube pass of a membrane module, and performing solvothermal synthesis to obtain a membrane module with a ZIF-8 (at) ZnO composite microrod array grown on the outer surface or the inner surface of the PVDF hollow fiber membrane; and injecting a silicone rubber solution into a shell pass or a tube pass of a membrane module, and drying and crosslinking to obtain the silicone rubber / MOF vertical array hollow fiber composite membrane. The hollow fiber composite membrane with the MOF directional molecular transfer channel is successfully constructed on the outer surface or the inner surface of the flexible hollow fiber membrane, directional transfer of guest molecules in the membrane is achieved, the mass transfer process of PV membrane separation is enhanced, and the ethyl alcohol / water separation performance is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of membrane separation, and in particular to a silicone rubber / MOF vertical array hollow fiber composite membrane and a preparation method and application thereof. Background Art

[0002] Excessive use of fossil fuels such as coal, oil, and natural gas can lead to global warming, environmental pollution, energy crisis and other hazards. Bioethanol can be used as a clean energy to replace fossil fuels due to its advantages such as renewability, high calorific value and environmental friendliness, serving my country's energy conservation and emission reduction. Separating bioethanol from fermentation broth can effectively improve the production efficiency of fermented ethanol. Pervaporation (PV) membrane separation technology has attracted widespread attention due to its advantages such as low energy consumption, high efficiency and harmlessness to microorganisms. As the core of the PV separation process, the preparation of high-performance PV membranes is crucial. Polymer hollow fiber membranes have become one of the most important membrane types in industrial applications due to their large packing density and effective area and strong self-support. Therefore, the preparation of high-performance PV membranes on the surface of polymer hollow fiber membranes has important scientific value and potential application value. The polymer membranes that are currently more commonly used are usually subject to the "trade-off effect" between permeability and selectivity, which makes the separation performance of polymer membranes poor.

[0003] MOFs are a new type of porous crystalline material. Due to their large specific surface area, pore structure and strong adsorption capacity, they are widely used in gas separation, catalysis and energy storage. In recent years, researchers have prepared continuous defect-free MOF-based membranes on the surface of hollow fiber membranes to improve membrane separation performance. Wang et al. prepared ZIF-8 membranes on the surface of polypropylene hollow fiber membranes through rapid current-driven synthesis. The prepared ZIF-8 membranes have a strong affinity for C 3 H 6 / C 3 H 8 Binary mixtures have excellent separation performance. After bending the ZIF-8 membrane, the separation performance of the ZIF-8 membrane remains unchanged (J.Am.Chem.Soc.2020,142,50,20915-20919). Hou et al. used dip coating technology to prepare a continuous flexible ZIF-8 membrane on the surface of a titanium-functionalized polymer hollow fiber membrane with good H 2 / CO 2Separation selectivity (Angew.Chem.Int.Ed.2016,55,3947-3951). These studies have actively promoted the application of MOF-based separation membranes in the field of gas separation. Patent CN202311699790.2 discloses that a continuous MOF polycrystalline base membrane is prepared on the inner surface of a polymer hollow fiber membrane by passing a metal salt solution and an organic ligand solution into a hollow fiber membrane assembly, and the silicone rubber / MOF hollow fiber composite membrane prepared after silicone rubber coating is used for ethanol / water separation. However, the improvement of ethanol-water separation performance in the prior art is still limited, and how to further improve the ethanol / water separation performance is of great research significance. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a silicone rubber / MOF vertical array hollow fiber composite membrane and a preparation method thereof for high-efficiency PV separation of ethanol / water solution.

[0005] Specifically, the present invention is achieved through the following solutions:

[0006] A method for preparing a silicone rubber / MOF vertical array hollow fiber composite membrane comprises the following steps:

[0007] 1) filling and sealing the polymer hollow fiber membrane in a tube, and naturally curing at room temperature to obtain a polymer hollow fiber membrane module, wherein the inner space of the polymer hollow fiber membrane is the tube side of the membrane module, and the space between the polymer hollow fiber membrane and the outer shell of the membrane module is the shell side of the membrane module;

[0008] 2) injecting the MOF precursor solution into the shell side or tube side of the membrane module moistened with methanol, removing the excess MOF precursor solution in the module after standing, and then placing it in an oven for self-crystallization to obtain a polymer hollow fiber membrane module containing MOF seeds;

[0009] 3) injecting a metal oxide precursor solution into the shell side or tube side of the membrane assembly and sealing the shell side or tube side port of the membrane assembly, and moving the membrane assembly to an oven for reaction; after the reaction is completed, pouring out the solution in the shell side or tube side of the membrane assembly and washing it, and placing it in an oven for drying to obtain a membrane assembly with a metal oxide rod array grown on the outer or inner surface of the polymer hollow fiber membrane;

[0010] 4) injecting the MOF organic ligand solution into the shell side or tube side of the membrane assembly, moving it to an oven for reaction, washing it after the reaction is completed to remove the unreacted organic ligand, and then moving it to an oven for drying to obtain a membrane assembly with a MOF / metal oxide rod array grown on the outer or inner surface of the polymer hollow fiber membrane;

[0011] 5) Injecting the silicone rubber mixed solution into the shell side or tube side of the membrane assembly, and after standing, placing the membrane assembly in an oven for cross-linking and curing to obtain the silicone rubber / MOF vertical array hollow fiber composite membrane.

[0012] Furthermore, in step 1), epoxy resin or 704 silicone rubber is used for sealing.

[0013] Furthermore, the hollow fiber membrane is a microfiltration membrane, an ultrafiltration membrane or a nanofiltration membrane; the polymer in the polymer hollow fiber membrane is polyvinylidene fluoride, polytetrafluoroethylene, polysulfone, polyethersulfone, polyethylene, polypropylene, and polyacrylonitrile.

[0014] Furthermore, the MOF organic ligand solution is a mixed solution comprising MOF organic ligand and a solvent.

[0015] Furthermore, the solvent is a mixed solvent of water and N,N-dimethylformamide in a volume ratio of 1:1 to 8. Preferably, the volume ratio of water to N,N-dimethylformamide is 1:2 to 4.

[0016] Furthermore, the MOF precursor solution is an aqueous solution containing metal ions and MOF organic ligands.

[0017] Furthermore, the metal ions and the metal in the metal oxide are both zinc or cobalt; and the MOF organic ligand is dimethylimidazole or 4,5-dichloroimidazole.

[0018] Furthermore, the silicone rubber mixed solution is obtained by dissolving silicone rubber, a crosslinking agent and a catalyst in an organic solvent.

[0019] Furthermore, the silicone rubber is polydimethoxysiloxane (PDMS), polymethylphenylsiloxane (PMPS) or polymethyloctylsiloxane (POMS); the crosslinking agent is tetraethyl orthosilicate (TEOS), phenyltrimethoxysilane (PTMOS), octyltrimethoxysilane (OTMOS) or γ-aminopropyltriethoxysilane (APTEOS); the catalyst is dibutyltin dilaurate (DBTDL) or di-n-octyltin dilaurate (DOTDL); and the organic solvent is n-heptane, n-hexane or n-pentane.

[0020] Furthermore, the mass ratio of the organic solvent, the silicone rubber, the crosslinking agent and the catalyst is 100-1000: 0.5-5: 0.1-1: 0.02-0.2.

[0021] Furthermore, in step 2), the membrane assembly wetted with methanol is obtained by injecting methanol into the shell of the membrane assembly, allowing the membrane assembly to stand for 10 to 60 minutes, and then removing excess methanol in the assembly to obtain a membrane assembly in which the polymer hollow fiber membrane is wetted with methanol.

[0022] Further, in step 2), specifically: according to the ratio of 0.1-2g of zinc nitrate hexahydrate, zinc acetate or cobalt nitrate hexahydrate to 10mL of deionized water, zinc nitrate hexahydrate, zinc acetate or cobalt nitrate hexahydrate is added to deionized water to obtain solution 1; according to the ratio of 1-10g of dimethylimidazole or 4,5-dichloroimidazole to 100mL of deionized water, dimethylimidazole or 4,5-dichloroimidazole is added to deionized water, and stirred at 100-300rpm for 10-60min to obtain solution 2. Solution 1 is added to solution 2, and stirred at 100-300rpm for 10-60min to obtain a MOF precursor solution. The obtained MOF precursor solution is injected into the shell of the hollow fiber membrane assembly wetted with methanol. After standing for 10 to 60 minutes, the excess MOF precursor solution in the assembly is removed, and then the membrane assembly is placed in a 40 to 60°C oven for self-crystallization for 0.5 to 2 hours to obtain a polymer hollow fiber membrane assembly containing MOF seeds.

[0023] Further, in step 3), specifically: according to the ratio of 1 to 5 g of zinc nitrate hexahydrate, zinc acetate or cobalt nitrate hexahydrate per 25 mL of deionized water, zinc nitrate hexahydrate, zinc acetate or cobalt nitrate hexahydrate is added to deionized water, and stirred at room temperature for 10 to 30 min to fully dissolve it, to obtain solution 3; according to the ratio of 2 to 6 g of sodium hydroxide or ammonia water per 25 mL of deionized water, sodium hydroxide or ammonia water is added to deionized water, and stirred at room temperature for 10 to 30 min to fully dissolve it, to obtain to solution 4; adding solution 3 to solution 4, stirring at room temperature for 10 to 30 minutes to obtain a metal oxide precursor solution; wherein the volume ratio of solution 3 to solution 4 is 1:0.5 to 2; injecting the metal oxide precursor solution into the shell side of the membrane component obtained in step 2) and sealing the shell side port of the membrane component; then subjecting the sealed membrane component to a hydrothermal reaction at 40 to 100° C. for 6 to 24 hours, discharging the solution in the membrane component after the reaction, and washing and drying with ethanol to obtain a membrane component with a metal oxide rod array grown on the surface of the polymer hollow fiber membrane.

[0024] Further, in step 4), specifically: according to the ratio of 0.5-3g of dimethylimidazole or 4,5-dichloroimidazole to every 3.6mL of deionized water and N,N-dimethylformamide mixed solution with a volume ratio of 1-4:1-8, dimethylimidazole or 4,5-dichloroimidazole is added to a mixed solution of deionized water and N,N-dimethylformamide with a volume ratio of 1:1-8, and stirred at room temperature for 20 minutes to obtain a MOF organic ligand solution; the MOF organic ligand solution is injected into the shell of the membrane component obtained in step 3), the membrane component is sealed, and after reacting at 50-100°C for 3-18 hours, the solution in the membrane component after the reaction is discharged, and after washing and drying with methanol, a membrane component with MOF / metal oxide rod array grown on the surface of the polymer hollow fiber membrane is obtained.

[0025] Furthermore, in step 5), specifically: add silicone rubber, a cross-linking agent and a catalyst to an organic solvent, stir for 1 to 3 hours to obtain a silicone rubber mixed solution, inject the silicone rubber mixed solution into the shell side of the membrane component obtained in step 4), let it stand for 0.5 to 10 minutes, then remove the solution in the shell side of the component and thermally cross-link at 60 to 120°C for 4 to 12 hours to obtain a silicone rubber / MOF vertical array hollow fiber composite membrane.

[0026] The present invention also provides a silicone rubber / MOF vertical array hollow fiber composite membrane prepared by the above preparation method.

[0027] The present invention also provides application of the silicone rubber / MOF vertical array hollow fiber composite membrane in ethanol / water separation.

[0028] Beneficial effects:

[0029] 1. The present invention adopts a membrane-making strategy to prepare a polymer / MOF composite separation membrane by preferentially constructing a MOF functional layer on the surface of a polymer hollow fiber membrane and then modifying the polymer, which successfully solves the problem of membrane-making failure or separation layer non-uniformity caused by the gravity of the casting liquid itself when preparing the separation layer by the traditional coating method. It provides a new idea for the uniform preparation of polymer / MOF hollow fiber separation membranes.

[0030] 2. The present invention uses metal oxide rods, especially ZnO rods, as sacrificial templates to successfully construct MOF vertical directional molecular transfer channels on the surface of polymer hollow fiber membranes without the need for additional Zn sources, thereby achieving directional and rapid transfer of guest molecules in the membrane during PV separation, strengthening the mass transfer process of molecules in the membrane, and improving membrane permeability.

[0031] 3. Thanks to the micro-nano structure of the MOF / metal oxide composite rods on the membrane surface and the simple coating process, the defects of the ZIF-8 layer were repaired without changing the array structure. The prepared silicone rubber / MOF vertical array composite membrane exhibits superhydrophobicity, effectively reducing the penetration of water molecules in the membrane and improving the membrane separation selectivity.

[0032] 4. The unique array structure on the surface of the silicone rubber / MOF hollow fiber composite membrane prepared by the present invention increases the actual separation area of ​​the membrane and effectively improves the separation capacity of the polymer / MOF array composite membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a transmission electron microscope image of the composite rods in the membrane surface array structure of Example 1 of the present invention.

[0034] Figure 2 The surface and cross-sectional SEM images of the silicone rubber / MOF vertical array hollow fiber composite membrane obtained in Example 1 of the present invention.

[0035] Figure 3 This is a cross-sectional SEM image of the silicone rubber hollow fiber composite membrane obtained in Control Example 1 of the present invention.

[0036] Figure 4 The surface and cross-sectional SEM images of the MOF vertical array hollow fiber composite membrane obtained in Control Example 2 of the present invention.

[0037] Figure 5 It is a cross-sectional SEM image of the ZIF-8@ZnO / PVDF array membrane in Example 1, Example 2, Comparative Example 3 and Comparative Example 4 of the present invention that has not been treated by step 5).

[0038] Figure 6 The figure is a comparison result of the separation performance of Example 1 of the present invention and Comparative Examples 1 and 2.

[0039] Figure 7 The figure is a comparison result of the separation performance of Examples 1 and 2 of the present invention and Comparative Examples 3 and 4. DETAILED DESCRIPTION

[0040] The content of the present invention is further described below in conjunction with the accompanying drawings, embodiments and comparative examples, but the scope of protection claimed by the present invention is not limited to the following embodiments.

[0041] Embodiment 1:

[0042] A method for preparing a silicone rubber / MOF vertical array hollow fiber composite membrane, the specific steps are as follows:

[0043] 1) Five PVDF hollow fiber membranes (inner diameter, 750 μm; outer diameter, 1200 μm; porosity, 67.4%) were loaded into a glass tube, encapsulated with 704 silicone rubber, and dried at room temperature for 48 h to obtain a hollow fiber membrane assembly.

[0044] 2) Inject methanol into the shell of the membrane assembly, let it stand for 20 minutes, then remove the excess methanol in the assembly to obtain a PVDF membrane wetted with methanol hollow fiber membrane assembly. Add 0.5948g of zinc nitrate hexahydrate to 10mL of deionized water to obtain solution 1. Add 8.2g of dimethylimidazole to 500mL of deionized water and stir at 300rpm for 30min to obtain solution 2. Add solution 1 to solution 2 and stir at 230rpm for 15min to obtain a MOF precursor solution. Inject the obtained MOF precursor solution into the shell of the hollow fiber membrane assembly wetted with methanol, let it stand for 30min, remove the excess MOF precursor solution in the assembly, and then place the membrane assembly in a 50℃ oven for self-crystallization for 1h to obtain a PVDF hollow fiber membrane assembly containing MOF seeds.

[0045] 3) Prepare the concentration of 0.4 mol·L-1 Zn(NO 3 ) 2 6H 2 O and 4 mol·L -1 Then, 25 mL of NaOH solution was slowly added to the same volume of Zn(NO 3 ) 2 6H 2 O aqueous solution, stirred for 20 minutes until the solution was transparent, and a ZnO precursor solution was obtained. The ZnO precursor solution was injected into the shell side of the membrane assembly of the above-mentioned PVDF hollow fiber loaded with MOF crystal seeds, and the shell side port of the assembly was sealed, and moved to a 60°C oven for reaction for 18 hours. After the reaction was completed, the solution in the shell side of the membrane assembly was poured out and washed with ethanol three times, and then placed in a 60°C oven for drying for 6 hours to obtain a ZnO microrod array grown on the surface of the PVDF hollow fiber membrane.

[0046] 4) Add 0.1478 g of dimethylimidazole to H 2 O and DMF mixed solution, stirred for 20 min until dimethylimidazole was completely dissolved to make a concentration of 0.1 mol·L -1 The dimethylimidazole solution was then injected into the shell of the ZnO / PVDF array membrane assembly obtained above, and moved to a 70°C oven for reaction for 10 hours. After the reaction was completed, it was washed three times with methanol to remove the unreacted dimethylimidazole. The assembly was then moved to a 100°C oven for drying to obtain a ZIF-8@ZnO / PVDF array membrane (such as Figure 1 and Figure 5 (as shown in (a)).

[0047] 5) Add 0.2 g PMPS to 19.8 mL n-heptane and stir at 300 rpm for 20 min. Then, add 0.04 g TEOS and 0.008 g DBTDL to the above solution, stir at 300 rpm for 20 min, and inject into the shell of the ZIF-8@ZnO / PVDF array membrane assembly. After standing for 5 min, put the membrane assembly into an 80 ° C oven for cross-linking and curing for 4 h to obtain PMPS-ZIF-8@ZnO / PVDF array membrane (such as Figure 2 As shown, Figure 2 (a) and Figure 2 (b) is the surface SEM image. Figure 2 (c) is a cross-sectional SEM image).

[0048] Embodiment 2:

[0049] The only difference from Example 1 is:

[0050] In step 4), a volume ratio of 1:2 is used for H 2After the mixture of O and DMF (step 4) is completed, the product obtained is as follows Figure 5 (as shown in (b)).

[0051] Comparative Example 1:

[0052] The only difference from Example 1 is:

[0053] Without performing the steps 2), 3) and 4) of Example 1, a PDMS / PVDF hollow fiber membrane (such as Figure 3 shown).

[0054] Comparative Example 2:

[0055] The only difference from Example 1 is:

[0056] Without performing step 5 of Example 1, a ZIF-8@ZnO / PVDF array membrane (such as Figure 4 As shown, Figure 4 (a) and Figure 4 (b) is the surface SEM image. Figure 4 (c) and Figure 4 (d) is a cross-sectional SEM image).

[0057] Comparative Example 3:

[0058] The only difference from Example 1 is:

[0059] In step 4), a volume ratio of 2:1 was used for H 2 After the mixture of O and DMF (step 4) is completed, the product obtained is as follows Figure 5 (c)).

[0060] Comparative Example 4:

[0061] The only difference from Example 1 is:

[0062] In step 4), a volume ratio of 4:1 was used for H 2 After the mixture of O and DMF (step 4) is completed, the product obtained is as follows Figure 5 (d)).

[0063] The hollow fiber composite membrane modules obtained in each embodiment and control example were used to separate and recover ethanol from an ethanol aqueous solution to verify the molecular separation performance. The specific test standards are as follows:

[0064] The effective area of ​​the membrane used in the test is 15 cm 2The raw material liquid is 5wt% ethanol aqueous solution, the raw material liquid circulation flow rate is 0.5m / s, and the test system temperature is maintained at 40°C. A vacuum pump is used to keep the permeate pressure below 100Pa, and the collector is immersed in liquid nitrogen to collect the permeate vapor. The raw material liquid and permeate components are then tested using a GC-7890II gas chromatograph (China Tianmei Scientific Instrument Co., Ltd.), and each membrane assembly is measured at least three times. The total permeate flux (J, gm) is calculated according to the following equation: -2 .h -1 ) and separation factor (β):

[0065]

[0066] J i =J×m i (3)

[0067] where W (g) is the total mass of permeate collected in t hours, and A (m 2 ) is the effective area of ​​the membrane. m f and m p are the ethanol concentrations (wt %) on the feed side and the permeate side, respectively.

[0068] The separation performance comparison results of the hollow fiber composite membrane modules obtained in each embodiment and the comparative example are as follows: Figure 6 and Figure 7 As shown. Figure 6 It can be seen that the ethanol permeation flux and separation factor of the silicone rubber / MOF vertical array hollow fiber composite membrane in Example 1 reached 2 kg.m -2 .h -1 and 10.5. The separation performance is much higher than that of the silicone rubber hollow fiber composite membrane prepared in Control Example 1 (0.58 kg.m -2 .h -1 , 7.9). Thanks to the construction of the vertically oriented molecular transfer channel of MOF in the membrane and the array structure on the membrane surface, the boundary layer resistance is reduced during the separation process, breaking the "trade-off effect" between the permeability and selectivity of the pure silicone rubber membrane, and achieving a simultaneous improvement in membrane permeability and selectivity. The ethanol permeation flux of the MOF vertical array hollow fiber composite membrane prepared in Control Example 2 reached 1.65kg.m -2 .h -1, the separation factor is 6.3. It shows that the MOF layer, as a vertical directional molecular transfer channel in the membrane, has a certain separation effect on PV separation of ethanol and aqueous solution. After being coated with the silicone rubber matrix in Example 1, the separation performance of the membrane is significantly improved; its ethanol permeation flux is 1.1 times that of the MOF vertical array hollow fiber composite membrane prepared in Control Example 2, and the water permeation flux is 0.7 times that of the MOF vertical array hollow fiber composite membrane prepared in Control Example 2; the separation factor is 1.4 times that of the MOF vertical array hollow fiber composite membrane prepared in Control Example 2. It shows that the coating of the silicone rubber matrix significantly increases the dissolution selectivity of the membrane surface, increases the permeation of ethanol molecules, hinders the permeation of water molecules, and enhances the membrane separation performance.

[0069] like Figure 7 As shown in Figure 2, the ethanol permeation flux and separation factor of the silicone rubber / MOF vertical array hollow fiber composite membrane obtained in Example 2 reached 1.88 kg.m -2 .h -1 The ethanol flux was 0.9 times that of the composite membrane obtained in Example 1, and the separation factor remained stable. The ethanol permeation flux and separation factor of the silicone rubber / MOF vertical array hollow fiber composite membrane obtained in Comparative Example 3 were 1.58 kg.m -2 .h -1 The ethanol permeation flux of the silicone rubber / MOF vertical array hollow fiber composite membrane obtained in Control Example 4 dropped to 1.32 kg.m -2 .h -1 , the separation factor is 10.8. The ethanol permeation flux of the silicone rubber / MOF vertical array hollow fiber composite membrane obtained in Example 1 is 1.5 times that of the conventional one. Figure 5 It can be seen that with the increase of H 2 With the increase of O / DMF volume ratio, the dissolution rate of ZnO microrods is accelerated, and ZIF-8 will gradually be generated in the ligand solution between ZnO microrods, which will cause the microrod array structure to disappear and form a continuous ZIF-8 layer on the membrane surface. The thicker ZIF-8 layer increases the mass transfer resistance of guest molecules in the membrane, and this non-directional molecular channel will make the transfer of guest molecules in the membrane uncertain, increase the molecular transfer path, and thus reduce the permeation of ethanol and water molecules. In addition, due to the disappearance of the microrod array structure, the effective separation area of ​​the membrane surface will be reduced, and the flux of water and ethanol will be reduced. Since the reduction in ethanol flux is less than the reduction in water flux, the membrane separation factor increases slowly.

[0070] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a silicone rubber / MOF vertical array hollow fiber composite membrane, characterized in that: The steps include: 1) filling and sealing the polymer hollow fiber membrane in a tube, and naturally curing at room temperature to obtain a polymer hollow fiber membrane module, wherein the inner space of the polymer hollow fiber membrane is the tube side of the membrane module, and the space between the polymer hollow fiber membrane and the outer shell of the membrane module is the shell side of the membrane module; 2) injecting the MOF precursor solution into the shell side or tube side of the membrane module moistened with methanol, removing the excess MOF precursor solution in the module after standing, and then placing it in an oven for self-crystallization to obtain a polymer hollow fiber membrane module containing MOF seeds; 3) injecting a metal oxide precursor solution into the shell side or tube side of the membrane assembly and sealing the shell side or tube side port of the membrane assembly, and moving the membrane assembly to an oven for reaction; after the reaction is completed, pouring out the solution in the shell side or tube side of the membrane assembly and washing it, and placing it in an oven for drying to obtain a membrane assembly with a metal oxide rod array grown on the surface of the polymer hollow fiber membrane; 4) injecting the MOF organic ligand solution into the shell side or tube side of the membrane assembly, moving it to an oven for reaction, washing it after the reaction is completed to remove the unreacted organic ligand, and then moving it to an oven for drying to obtain a membrane assembly with a MOF / metal oxide rod array grown on the outer or inner surface of the polymer hollow fiber membrane; 5) Injecting the silicone rubber mixed solution into the shell side or tube side of the membrane assembly, and after standing, placing the membrane assembly in an oven for cross-linking and curing to obtain the silicone rubber / MOF vertical array hollow fiber composite membrane.

2. The preparation method according to claim 1, characterized in that: The hollow fiber membrane is a microfiltration membrane, an ultrafiltration membrane or a nanofiltration membrane; the polymer in the polymer hollow fiber membrane is polyvinylidene fluoride, polytetrafluoroethylene, polysulfone, polyethersulfone, polyethylene, polypropylene, and polyacrylonitrile.

3. The preparation method according to claim 1, characterized in that: The MOF organic ligand solution is a mixed solution containing MOF organic ligands and a solvent.

4. The preparation method according to claim 4, characterized in that: The solvent is a mixed solvent of water and N,N-dimethylformamide in a volume ratio of 1:1 to 8.

5. The preparation method according to claim 1, characterized in that: The MOF precursor solution is an aqueous solution containing metal ions and MOF organic ligands.

6. The preparation method according to claim 5, characterized in that: The metal in the metal ion and the metal oxide is zinc or cobalt; the MOF organic ligand is dimethylimidazole or 4,5-dichloroimidazole.

7. The preparation method according to claim 1, characterized in that: The silicone rubber mixed solution is obtained by dissolving silicone rubber, a crosslinking agent and a catalyst in an organic solvent.

8. The preparation method according to claim 7, characterized in that: The silicone rubber is polydimethoxysiloxane, polymethylphenylsiloxane or polymethyloctylsiloxane; the crosslinking agent is tetraethyl orthosilicate, phenyltrimethoxysilane, octyltrimethoxysilane or γ-aminopropyltriethoxysilane; the catalyst is dibutyltin dilaurate or di-n-octyltin dilaurate; and the organic solvent is n-heptane, n-hexane or n-pentane.

9. A silicone rubber / MOF vertical array hollow fiber composite membrane, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the silicone rubber / MOF vertical array hollow fiber composite membrane according to claim 9 in ethanol / water separation.

Citation Information

Patent Citations

  • Oil and water separator based on micron-nano hiberarchy net membrane and preparation and application method thereof

    CN102350094A

  • Highly-directional metal organic framework molecular sieve membrane and preparation method and application thereof

    CN107890752A

  • Method for preparing bimetallic MOF membrane by utilizing self-conversion of hydroxyl bimetallic salt and application of bimetallic MOF membrane in pervaporation separation

    CN111672341A

  • Mixed matrix membrane of bead-like MOF filled silicone rubber

    CN112316741A

  • Preparation method of ultrathin silicone rubber / MOF hollow fiber composite membrane

    CN116116241A

Cited By

  • A metal-organic framework hollow fiber membrane module with a detachable structure and its application in gas separation.

    CN122665487A